e-Biologics: Fabrication of Sustainable Electronics with “Green” Biological Materials - Derek R. Lovley (American Society for Microbiology, 2017)
ABSTRACT The growing ubiquity of electronic devices is increasingly consuming substantial energy and rare resources for materials fabrication, as well as creating expansive volumes of toxic waste. This is not sustainable. Electronic biological materials (e-biologics) that are produced with microbes, or designed with microbial components as the guide for synthesis, are a potential green solution. Some e-biologics can be fabricated from renewable feedstocks with relatively low energy inputs, often while avoiding the harsh chemicals used for synthesizing more traditional electronic materials. Several are completely free of toxic components, can be readily recycled, and offer unique features not found in traditional electronic materials in terms of size, performance, and opportunities for diverse functionalization. An appropriate investment in the concerted multidisciplinary collaborative research required to identify and characterize e-biologics and to engineer materials and devices based on e-biologics could be rewarded with a new “green age” of sustainable electronic materials and devices.